STRATIGRAPHY AND VOLCANISM IN THE EARLY PROTEROZOIC PECHENGA STRUCTURE (KOLA PENINSULA) - Smolkin V.F.; Skufin P.K.; Mitrofanov F.P.; Mokrousov V.A. (My University, 1996)
The Pechenga structure comprising sequences, which serve as the reference for the northeastern Baltic Shield, includes the northern and southern structural zones. Both zones are composed of sedimentary-volcanogenic rocks of the Karelian Complex (the Lower Karelian Eratem) metamorphozed under conditions of prehnite to pumpellyite facies. Based on published and new original data, the following formations are proposed to be defined in the northern zone (from the base upward): the Televi, Majärvi, Kuvernerinjoki, Pirttijärvi, Orshoaijvi, Luchlompolo, Zapolyarnyi, Zhdanov, Lammas, Matert, and Suppvaara formations correlative to the Sariolian, Jatulian, and Ludicovian (Ludian) of Karelia. In the southern zone, the Karelian complex is divided into the Kallojaur, Bragino, and Mennel' formations and Kaplya and Kasesjoki rock associations, which are referred to the Kalevian. The paleovolcanologic, formational, and geochemical analyses enabled the recognition of the basaltic andesite, trachybasalt, tholeiite, ferropicrite, picrite-basalt-andesite, and andesite-dacite-rhyolite volcanogenic formations, all formed during six megacycles of magmatism in the interval of 2350-1850 Ma. Metamorphism culminated at 1750-1700 Ma. The structural patterns of the sequences and geochemical and isotopic data agree with the model of intracontinental riftogenesis in the Pechenga-Varzuga belt, which experienced a complete cycle of development during the Early Proterozoic.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой